The impact of cooperative patronage: the case of National Small Holder Farmers' Association (NASFAM) of Malawi in Kasungu District - Matchaya, Greenwell C.; Perotin, V. (Informa UK Limited, 2013)
This paper analyses the impact of individual farmers' participation in the National Smallholder Farmers' Association of Malawi (NASFAM). Precisely the paper analyses the effect of participation on credit market access, fertilizer use and total incomes of its participants in the Kasungu district of Malawi. NASFAM is a form of producer cooperative with a number of socio-economic functions. Using data on income per capita, fertilizer expenditure and access to credit, this paper tests the hypothesis that participation in NASFAM positively impacted incomes, fertilizer use and credit acquisition. Employing Propensity Score Matching methodology to estimate Average Treatment Effects (ATT) on programme members, this paper finds evidence that participation in NASFAM had a positive effect on all the endogenous variables. Membership enhances household level incomes, fertilizer use and credit acquisition and is hence in line with national goals of poverty reduction, the Comprehensive African Agriculture Development Program (CAADP) principles, the SADC's Regional Indicative Strategy Development Plan (RISDP) and the achievement of the Millennium Development Goals. Based on these findings and the fact that credit and fertilizer access are still problematic in Malawi's rural areas, it appears that there is great need for NASFAM to expand to areas where it currently does not have activities. Such expansion would ensure food security over a wider range of rural households through improved input access.